LEARNERS’ PERCEPTIONS OF NATIVE-SPEAKER INTERVIEWS AS A STRATEGY FOR IMPROVING ENGLISH PROFICIENCY - Jimmi, Jimmi; Wibowo, Ari Iswanto; Purwaningrum, Prapti Wigati; Priyatmojo, Arif Suryo (Universitas Negeri Semarang, 2025)
This study examines the perspectives of non-English major students regarding the role of interviewing native speakers in enhancing their English proficiency at a public online institution in Indonesia. A mixed-method design with a sequential explanatory approach was implemented. Quantitative data were collected from 50 non-English major students using a Google Form questionnaire and subjected to descriptive analysis to discern overarching perceptual trends. After that, we looked at the open-ended responses qualitatively to find out more about the things that were shaping those perceptions. The results show that most students think that interviewing native speakers is challenging and interesting way to improve their speaking confidence, listening comprehension, and vocabulary since they have to use English directly with the native speakers. The qualitative findings indicate that students regard the activity as a genuine learning experience that enhances real-life communication and boosts their enthusiasm to actively engage with English. In conclusion, the study indicates that incorporating interviews with native speakers is an effective pedagogical strategy for enhancing English competence among learners from non-English academic backgrounds.